Assessing the salinity effects and economic feasibility of on-farm desalination technology in irrigated semi-arid regions - Barnes, Kaitlyn, author; Bailey, Ryan, advisor; Sharvelle, Sybil, committee member; Melzer, Suellen, committee member (Colorado State University. Libraries, 2021)
High salinity levels in areas with intensive agricultural practices can inhibit agricultural productivity. Semi-arid regions where irrigation is used to support crop growth are particularly impacted by the quality of surface and groundwater sources. In this study, we use a combined numerical modeling and economic analysis approach to estimate the regional impact of an on-farm desalination technology on multi-decadal salinity fate and transport and explore whether the technology is viable to improve soil health, crop yield, and long-term profitability. A subsurface salt transport model (MODFLOW-RT3D) is applied to a 50,600-ha (125,000 acres) region in southeastern Colorado located within the Arkansas River Valley. The model simulates the reactive transport in soils and groundwater of 8 major salt ions (Ca+, Mg2+, Na+, K, SO42-, CO32-, HCO3-, and Cl-). Simulated values of average soil water concentration (TDS) are used to estimate crop relative yield with and without salt removal at various removal rates (Baseline – no salt removed; Unit removal – average of 60% salt removed; 100% salt removal) and time periods (5, 10, 15, 20, 25 years after desalination begins). The Unit removal rate is calibrated to align with a solar powered, reverse-osmosis desalination system that is currently being tested in semi-arid study area. For the Unit rate of 60% salt removal, the average TDS of the study area was found to decrease by an average of 20% over a period of 20 years, resulting in an increase in crop yield of 1.6 – 2.3%. Using data on regional production costs, crop prices, and the costs of building and operating the desalination system, we calculate the Net Present Value of production with the desalination unit. The results indicate that desalination does increase economic returns, particularly for high-valued specialty crops, such as melons and onions; however, these benefits are considerably less than the costs of operating the desalination technology.
Keywords: desalination; natural resources; soil health; hydrologic modeling; crop production; semi-arid